Cytotoxic Activity of Cambodian Leaves Extract (Plumeria acuminate) on Breast Cancer Cells and COX-2 Targeted Prediction of Its Chemical Contents - Rahmah, Inggita Hasi; Harsan, Hayfa Salsabila; Rahman, Faaza Aulia; Meiyanto, Edy; Susidarti, Ratna Asmah (Indonesian Journal of Cancer Chemoprevention, 2023)
Cambodian leaves are suspected to contain stigma sterol which may target Cyclo-Oxygenase-2 (COX-2) or Estrogen Receptor (ER) to contribute to its cytotoxic activity on breast cancer cells. This study aimed to determine the potential of Cambodian leaf compounds and extracts as chemopreventive agents for luminal breast cancer with a molecular target of COX-2. Ethanol was used to extract the active compound of Cambodian leaves. The study on chemical activity against COX-2 employed molecular docking with Molecular Operating Environment (MOE) and the cytotoxic property of Cambodian leaf extract (CLE) on T47D was determined using the trypan blue exclusion method. The extraction yielded as 4.87% w/w CLE. Thin layer chromatography showed that Cambodian leaves contain sterol. Molecular docking confirmed that several sterol compounds have greater affinity to COX-2 than native ligands indicating that they are potent as COX-2 inhibitors. They are Stigmast-7-en-3-ol, Lupeol Acetate, and Lupeol carboxylic acid with docking scores of -14.3874, -13.8098, and -14.1045 kcal/mol respectively. The CLE exhibited cytotoxic activity on T47D cells with an IC50 value of 18 μg/mL. Therefore, CLE has a potential effect as a chemopreventive agent for breast cancer and potentially as a COX-2 inhibitor.Keywords: Cambodian leaf extract, breast cancer, COX-2 inhibitor, chemopreventive.